Tumor Markers and Cortisol Metabolism in Obesity - Akiibinu, Moses O.; Soile, Bob O.; Amzat, Ajibola M. U.; Kolawole, Oyetunji T. (Highlights on Medicine and Medical Research Vol. 10, 2021)
Obesity is a medical condition characterized by an excessive accumulation of body fat with consequent metabolic syndrome. In obesity, modulation of metabolic pathways plays critical roles in the pathogenesis of many diseases. Our study linked obesity, metabolic stress and tumor by evaluating the levels of tumor markers and cortisol (a stress-induced hormone) in obese individuals. Thirty-three obese (18 males, 15 females, body mass index=34 ± 3.8 Kg/M2) and 37 apparently non-obese (19 males, 18 females, body mass index=22 ± 1.4 Kg/M2) individuals (controls) volunteered to participate in this study. All participants were not on drugs (i.e. alcohol, cigarette or steroids) and were healthy adults without apparent medical problems. Every participant had his/her body weight and height taken, and the body mass index (BMI) calculated before inclusion in the study. Obesity was defined by using the body mass index (BMI; Kg/M2), where a BMI higher than 25 Kg/M2 was used as an index of overweight, while a BMI higher than 30 Kg/M2 was used as a cut-off point to indicate obesity. Plasma levels of carbohydrate antigen 125 (CA125), carcinoembryonic antigen (CEA), alpha fetoprotein (AFP) and cortisol were determined in these subjects using enzyme linked immunosorbent assay methods. In the obese subjects, plasma levels of CA125 and cortisol increased significantly (p<0.05), while plasma levels of CEA and AFP did not show significant (p>0.05) changes compared with controls. Metabolic changes could account for the increased rate of synthesis of cortisol and CA125 in obesity.